Dísticos elegíacos en Carducci (“Nevicata”, Odi Barbare, II) - Paraíso, Isabel (Rhythmica. Revista Española de Métrica Comparada, 2019)
Las Odi Barbare de Giosuè Carducci constituyen un hito mundial en la poesía que imita las formas métricas grecolatinas, tanto por su altura poética como por su precisión técnica. Carducci sortea el insoluble problema de trasvasar los esquemas cuantitativos clásicos mediante el sistema acentual italiano y la reproducción rítmica del modelo. Dentro de los 55 textos que componen las Odi Barbare, hemos escogido, para su traducción y exégesis, el poema “Nevicata”. Está escrito en dísticos elegíacos griegos, canónicamente compuestos por un hexámetro y un pentámetro. Con su métrica clasicista, Carducci renueva la poesía italiana moderna, y se convierte en referencia permanente para la poesía occidental. Giosuè Carducci’s Odi Barbare is a paramount reference for modern poetry in the Western world. Their technical perfection and their poetic excellence grant them a leading place among poems which imitate classical versification. As it is impossible to use long and short syllables in modern languages to reproduce Greek and Roman schemes of poetry, Carducci employs a blend of stressed and unstressed syllables to imitate the rhythm of his models. From the 55 Odi Barbare, we have selected “Nevicata” to be translated and studied. Its pattern is Greek elegiac couplet (or distich), composed of a hexameter and a pentameter. Odi Barbare by Carducci stimulates and innovates the modern Italian poetry. It becomes a permanent reference for poetry in our Western culture.